2019
DOI: 10.3389/fpsyt.2019.00234
|View full text |Cite
|
Sign up to set email alerts
|

Altered Local and Large-Scale Dynamic Functional Connectivity Variability in Posttraumatic Stress Disorder: A Resting-State fMRI Study

Abstract: Posttraumatic stress disorder (PTSD) is a psychiatric condition that can emerge after exposure to an exceedingly traumatic event. Previous neuroimaging studies have indicated that PTSD is characterized by aberrant resting-state functional connectivity (FC). However, few existing studies on PTSD have examined dynamic changes in resting-state FC related to network formation, interaction, and dissolution over time. In this study, we compared the dynamic resting-state local and large-scale FC between PTSD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
(69 reference statements)
0
13
0
Order By: Relevance
“…The spontaneous neuronal activation observed during resting state functional magnetic resonance imaging (fMRI) is frequently utilized to illustrate psychopathological alterations in cortical and in subcortical brain networks in psychiatric disorders, serving as a key biomarker in post-traumatic stress disorder (PTSD). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Importantly, emerging evidence has underscored the importance of incorporating deep-layer midbrain/brainstem neural circuits into the neurobiological framework of PTSD. 1,2,[15][16][17][18][19] The reticular activation system (RAS) serves a fundamental role toward the gating of salient, environmental information to higher order, cortical brain structures to facilitate the generation and the maintenance of an arousal state.…”
Section: Introductionmentioning
confidence: 99%
“…The spontaneous neuronal activation observed during resting state functional magnetic resonance imaging (fMRI) is frequently utilized to illustrate psychopathological alterations in cortical and in subcortical brain networks in psychiatric disorders, serving as a key biomarker in post-traumatic stress disorder (PTSD). [1][2][3][4][5][6][7][8][9][10][11][12][13][14] Importantly, emerging evidence has underscored the importance of incorporating deep-layer midbrain/brainstem neural circuits into the neurobiological framework of PTSD. 1,2,[15][16][17][18][19] The reticular activation system (RAS) serves a fundamental role toward the gating of salient, environmental information to higher order, cortical brain structures to facilitate the generation and the maintenance of an arousal state.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the decreased ReHo value in the right angular was negatively correlated with the symptom severity of PTSD (CAPS score). In our previous study of dynamic functional connectivity of PTSD, we found a decreased dynamic functional connectivity in the angular gyrus (Fu et al, 2019). Previous diffusion tensor imaging also found a diminished subcortical integrity in angular gyrus (Schuff et al, 2011).…”
Section: Discussionmentioning
confidence: 76%
“…Dynamic seed-based RSFC analysis for each participant was performed using the Temporal Dynamic Analysis toolkits that were based on DPABI V4.5 (also see Chen et al, 2019; Fu et al, 2019; Yan et al, 2017; Zhang et al, 2018 with DPARSF or DPABI). Sliding window-based analysis, which is sensitive to time-dependent variations (Chen et al, 2019; Hindriks et al, 2016; Liu et al, 2017; Yip et al, 2017), was applied to examine the seed-based RSFC over the whole brain.…”
Section: Methodsmentioning
confidence: 99%
“…Dynamic RS-fMRI has been used to analyze and identify the time-varying and recurring RS-fMRI subpatterns of coupling among brain regions to create the brain “chronnectome” (Calhoun et al, 2014; Filippi et al, 2019). Researchers have recently improved the analytical methods for dynamic RS-fMRI by using sliding window analysis (i.e., correlations among discrete large-scale brain regions with a short and sliding temporal window; Fong et al, 2019; Fu et al, 2019; Handwerker et al, 2012; Liu et al, 2017; Yan et al, 2017).…”
mentioning
confidence: 99%